Association between the triglyceride glucose body mass index and asthma: evidence from NHANES 2011–2018 - Sijia Yu; Shiping Wu; Shouxin Wei (BMC Pulmonary Medicine)
Abstract Background Asthma is a common chronic respiratory disease whose increasing prevalence poses a significant burden to human health and the economy. Several studies indicate that insulin resistance (IR) is associated with asthma development. The triglyceride-glucose body mass index (TyG-BMI) is a novel biomarker used to evaluate insulin resistance; however, limited research exists on the relationship between TyG-BMI and asthma. This study aimed to investigate the relationship between TyG-BMI and asthma in U.S. adults. Method This cross-sectional study utilized data from the National Health and Nutrition Examination Survey (NHANES) database for the 2011–2018 cycles. The exposure variable was the TyG-BMI of participants at baseline, which was calculated based on triglycerides (TG), fasting blood glucose (FBG), and body mass index (BMI). The primary outcome variable was asthma status, determined via questionnaire. We analyzed participants’ baseline characteristics and employed weighted multivariate logistic regression models to assess the correlation between TyG-BMI and asthma. A subgroup analysis was conducted to assess whether the relationship between TyG-BMI and asthma was influenced by other factors. Results In total, 8,553 participants were analyzed, revealing a positive association between TyG-BMI and asthma. In the analysis of TyG-BMI as a continuous variable, after adjusting for confounding variables, the Odds ratio (OR)(95% CI) for the association between TyG-BMI and asthma was 1.003. After further dividing TyG-BMI into quartiles and adjusting for potential confounders in Model 3, the prevalence of asthma was 0.561 times higher in those with the highest TyG-BMI than in those in the lowest quartile (OR: 1.561, 95% CI: 1.181, 2.065). There was a significant interaction between asthma and TyG-BMI among subgroups defined by gender, coronary heart disease, and stroke (interaction P < 0.05). Conclusions This cross-sectional study found a positive association between TyG-BMI and asthma. These results suggest that TyG-BMI has the potential to be used as an indicator to monitor the prevalence of asthma, but further longitudinal studies are needed to confirm causality and to assess its utility in the management of long-term comorbidities. Clinical trial number Not applicable.